Does persistence in start-up activity reflect persistence in social capital? - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2015)
Emerging literature shows that spatial differences in entrepreneurship tend to persist over longer periods of time. A potential mechanism underlying this pronounced persistence is that high levels of start-up activity lead to the emergence of a regional culture and a supporting environment in favor of entrepreneurship that particularly involves social capital. This chapter summarizes the available empirical evidence on the regional persistence of entrepreneurship and elaborates in detail how different elements of such a culture, such as social capital, can exert an influence on the level of new business formation and self-employment. As a demonstration for the relevance of a regional entrepreneurship culture for new business formation, we highlight the case of Germany where we find pronounced persistence of start-up activity despite radical structural and institutional shocks over the course of the 20th century. The German case suggests that there is a long-lasting local culture of entrepreneurship that can survive disruptive changes. We discuss the relationship between place- specific social capital and a regional culture of entrepreneurship and draw policy conclusions.
Keywords: L26; R11; O11; 330; economic development; entrepreneurship; entrepreneurship culture; institutions; new business formation; self-employment; social capital